PENGARUH MANAJEMEN RANTAI PASOKAN TERHADAP KINERJA UMKM BATIK DI PEKALONGAN - Kurniawan, Ardy; Kusumawardhani, Amie (Diponegoro Journal of Management, 2017)
SMEs that produce batik is one of leading sectors to boost Pekalongan's economy. In producing and distributing, it needs support by suppliers, distributors, retailers, also consumers. This research aims to analyze the influence of supply chain management to the performance of batik SMEs in Pekalongan by using four independent variables of information sharing, trust, long-term relationship, and collaboration.The object of this research is batik SMEs domiciled in Pekalongan. The number of samples is 100 owners or managers batik SMEs in Pekalongan by using analytical method is multiple regression analysis and operated by SPSS 23.The result shows that information sharing has a positive influence on supply chain management performance, trust has a positive effect on supply chain management performance, long-term relationship has a positive effect on supply chain management performance, and collaboration has a positive influence on supply chain management performance.